2009
DOI: 10.3382/ps.2008-00494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aflatoxin culture on intestinal function and nutrient loss in laying hens

Abstract: The negative effects of aflatoxins (AFLA) on hepatic necrosis and total tract digestibility of energy, N, and amino acids have been well documented. However, the question remains if this is an effect on nutrient metabolizability alone or an effect on the intestine, or both, resulting in increased endogenous nutrient loss or reduced nutrient retention, or both. Therefore, a 2-wk feeding study with a crude AFLA culture was conducted with laying hens to measure endogenous losses and digestive functionality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 24 publications
7
45
1
Order By: Relevance
“…Ali et al [13] reported that the toxicity of aflatoxin was characterized by reduction in body weight gain as aflatoxins interfere with normal metabolic pathway through the inhibition of protein synthesis and enzyme system that is involved in carbohydrate metabolism and energy release. The results of present study agree with data showing that AF contamination did not affect the liveability, egg production and feed intake of laying hens [5,19,28,29,31] . However, some researchers did report that dietary AF decreased egg production and feed intake [8,32,33] .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Ali et al [13] reported that the toxicity of aflatoxin was characterized by reduction in body weight gain as aflatoxins interfere with normal metabolic pathway through the inhibition of protein synthesis and enzyme system that is involved in carbohydrate metabolism and energy release. The results of present study agree with data showing that AF contamination did not affect the liveability, egg production and feed intake of laying hens [5,19,28,29,31] . However, some researchers did report that dietary AF decreased egg production and feed intake [8,32,33] .…”
Section: Discussionsupporting
confidence: 83%
“…In another study, the inclusion of dietary AFB 1 from 0 to 2.0 ppm resulted in lowered egg weight and nitrogen retention [28] . However, in 2-week a short feeding study, AF contamination did not have any detrimental effect on body weight gain [29] . Aflatoxin appears to exert its negative effect on animal performance chiefly by depressing the DNA and RNA synthesis and eventually protein synthesis [28,30] .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with the results of Kermanshahi et al (2007) in broilers and Applegate et al (2009) in laying hens. However, there was a trend that showed a decrease in the apparent digestibility of dry matter, organic matter, crude protein, and gross energy of the broilers feed diets when contaminated with AFB 1 and AFB 2 (P > 0.05).…”
Section: Nutrient Digestibilitysupporting
confidence: 83%
“…Furthermore, the type and specific line of chicken used in various studies may also affect the reaction of intestine towards chronic aflatoxicosis. This hypothesis is supported by the recent observations regarding aflatoxicosis in layers (Hyline W36; exposure age from 140 to 154 days) by Applegate et al (2009). Contrary to the observations in broilers, these authors noted a linear increase in the crypt depth in distal jejunum with the increasing levels of AFB1 in the diet as 0, 0,6, 1,2, and 2,5 mg/kg, but no effect of the toxin on villus height and number of toxins.…”
Section: Derlemecontrasting
confidence: 53%